The Ely memoranda and the economy of the late Anglo-Saxon fenland. (24th July 2017) - Naismith, Rory
Abstract: Consisting of six short Old English texts written in the early eleventh century, the Ely memoranda illustrate how a major and recently refounded Benedictine abbey managed its landed endowment. Two of the memoranda relate to generous help provided by Ely to Thorney, and four concern Ely's own lands. The collection as a whole reveals much about interaction between monasteries, monastic perspectives on material resources and investment in them, the economy of eastern England, and the context of record-keeping. This article offers a new edition and translation of the texts, and surveys the contribution the memoranda make to understanding of cultural and economic history.